Pengupahan Berkeadi lan Menurut Hukum Islam, Kajian terhadap UMP Jakarta - Eva Zulfa N (JURNAL INDO-ISLAMIKA, 2015)
The disertation is to prove that there was a wrong government policy of establishing the Provincial Minimum Wage reffering to the living cost for single. Because of such reason, the wage paid to labour is always insufficient to meet the living cost for labour and his family. The minimum wage should cover the operational cost of labour, so they can work fully during one month. The data of the minimum wage applied in in Pulau Gadung Estate, Jakarta (JIEP) showed that the wage paid to workers were only able to survive. If the policy is continued to be kept, the labour can not improve their living quality, and event the labour will be poor forever.This disertation is an alternative solution to overcome low wage happened in Indonesia. The system found will result the optimalization of labour income as their right must be gained from the company, and further effect to the company, the company will gain more profit, and event the company will develop its business optimally. Wage labour system will combine shirkah-inanwaal-ijarah so it will have a form of sharing any profit among labour, management power and stake holder. Besides, the labour will get wage proper basic wages including basic salary and benefit.The disertation refuses the views:  firstly, employers and the Indonesia government bureaucracy have created the labour as a part of production, effientcy and attractor for investation with low wages. Secondly, Jack Stiber says that workers are human resource belong to companies like other resources such as machine, material, money and method. As a result, workers must be ready for ending their works anytime. For management, the workers can be conside, as things like other sources. This ways resulted outsourcing method of employing labour. Thirdly, a view of Abdurahman al-Maliki, said that the policy of wage is based on estimation of experts in manpower market stock exchange.This dissertation has supported related to the Naqvi’s opinion about the distribution of income should be separated from the concentration of the economic power dominated by certain people, but the economic power must orientate to maximize the total welfare. The dissertation also improve the opinion of Joseph Qardawi starting that wages of labour is given on basis of value of his  work and it is not just enough to eat and drink as a replacement  for the lost power, but the wage must also consider the workers’ participation as a profit generator. Mustajir must pay full wages ajir event though the workers are willing to accept under proper wage. According to the opinion of Banisadr, Islam  rejects all concepts related to the application where the human beings or some of the people receive and get a bigger wage than the others who out of their responsibility. Abdul Jalil combine the wage system between the principal wage with the incentive (gainsharing) with the term combination called as shirkah inanwa al-ijarah which is still normative. Thus, the three opinions above cannot be applied in the waging system in increasingly complex companies.This dissertation is a case study observing labour wage system in Jakarta Industrial Estate Pulogadung in view of business  men, labour  and goverment. The primary data was randomly gained through quesionares  and deep interview comparing with constitution nomor 13, 2003 and Islamic wage concept. The Interpretation of Islamic wage concept uses fenomenology method which is a research method that mixed a subjective interpretation in observation object. The involvement of researcher in the field observing the object becomes standard pattern.